Four pedagogical models using video as a tool for learning in a distance teacher training program context - Florian Meyer; Roselyne Lampron; Marc-André Gazé (Firenze University Press, 2014)
The University of Sherbrooke offers online teacher training programs. Although the use of video in teacher training programs is a subject of current research, pedagogical models implemented by teacher trainers in Québec are still sparsely explored, especially in the context of distance learning. This article introduces the first step of a research that aims to understand - in a distance learning environment - the evolution of the interactions between teachers analyzing videos. The article specifically discusses the characteristics of pedagogical models implemented by four trainers. The analysis of these models is first presented. We secondly present the analysis of the specific activities using videos. Then, a typology of online interactions (Dumont, 2007) allows us to characterize the roles of the trainers. The article concludes with a reflection on the effectiveness of the described pedagogical models and further improvements to consider.   L'Università di Sherbrooke offre alcuni programmi di formazione per insegnanti completamente online. Sebbene l'uso di video nei programmi di formazione degli insegnanti sia attualmente oggetto di ricerca, i modelli pedagogici attuati dai formatori in Québec sono ancora scarsamente esplorati. Il presente articolo introduce la prima fase di una ricerca che mira a comprendere - in un ambiente di apprendimento a distanza - l'evoluzione delle interazioni tra insegnanti nell'analisi di video. L'articolo discute in particolare le caratteristiche dei modelli pedagogici attuati da quattro formatori che hanno partecipato alla ricerca. In primo luogo presentiamo l'analisi di questi modelli. In secondo luogo presentiamo l'analisi delle specifiche attività che utilizzano il video. Infine, una tipologia di interazioni online (Dumont, 2007) ci consente di caratterizzare il ruolo dei formatori. L'articolo si conclude con una riflessione sull'efficacia dei modelli pedagogici descritti e ulteriori miglioramenti da considerare.